Parenting Approaches Based on Stories from the Quran - Husna binti Husain, Zanariah Noor, Noor Banu Mahadir Naidu, Mohd Aderi Che Noh (International Journal of Advanced Science and Technology, 2020)
Parenting technique is one of the most important aspects in raising children in a family. However, effects of technological developments and influence of Western thoughts and also parents’ lack of exposure to parenting knowledge especially knowledge based on Islam, has caused parents to be more inclinedtowards Western parenting models, thus abandoning more suitable parenting guidelines based on the teachings of Islam. Without realizing, the Quran through many of its stories have shown its own parenting techniques which should be followed by Muslims to raise and educate their children. Thus, this study attempts to identify the parenting methods extracted from stories in the Quran. This study is a qualitative study that involves gathering of data related to tafseer of Quranic stories from primary and secondary sources, and comprehensive analysis were made to produce a parenting approach based on Quranic stories. Parenting approach based on the Quran is a perfection of Islamic parenting methods which are commonly practiced currently, in an effort to improve and solidify the Muslim parenting styles, at the same time providing the best alternative for the best parenting method suited for Muslims.